FAKTOR – FAKTOR YANG MEMPENGARUHI PEMANFAATAN PELAYANAN PENGOBATAN INFEKSI MENULAR SEKSUAL (IMS) DI PUSKESMAS PURWOKERTO SELATAN KABUPATEN BANYUMAS. - Arif Kurniawan; Arih Diyaning Intiasari (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2012)
ABSTRACT South Purwokerto is a region that also has high risk of Sexual Transmitted Infection (IMS) because there are wild prostitution areas which located in ex terminal and Rajawali Cinema. Based on data, curative service exploiting in Puskesmas Baturaden II have been good enough that equals to 83,93%, while in Puskesmas Purwokerto Selatan shows number of patients exploiting therapy service of IMS still be low that equals to 37,5%. This research aims to know service exploiting of Sexual Transmitted Infection ( IMS) therapy at IMS patient and factors influencing service exploiting of IMS therapy. The type of this research is survey with form of explanatory research. Population of this research is society in the job region of Puskesmas Purwokerto Selatan who have high risk of IMS. The sample number of this research is 40, obtained from formula of minimum sample size. Result of research shows that there is correlation between knowledge about therapy service of IMS, promotion of therapy service of IMS, and quality of therapy service of IMS with service exploiting of therapy IMS. While there is no correlation between service reachability of IMS therapy and service need of IMS therapy with service exploiting of IMS therapy. There is simultanous influence between promotion of IMS therapy service and quality of IMS therapy service with service exploiting of IMS therapy. Suggestion in this research is puskesmas must increase promotion of therapy service of IMS to the society in puskesmas region and increase quality of therapy service of IMS to the patient of IMS therapy. Kata Kunci : Pemanfaatan,Pengobatan, Infeksi Menular Seksual Kesmasindo Volume 5( 1)Januari 2012, hlm. 33-43